SHARE CAPITAL IN FOREIGN EXCHANGE ACCOUNTING. - Fuerst, E. (The Accounting Review, 1954)
Abstract It is an established principle of accountancy that assets and liabilities which are expressed in a currency other than that in which the capital is expressed, are to be converted into the currency of the capital. This principle follows quite naturally from the fundamental proposition that accounting is the art to record the history of a capital in the sense of a fund set aside for a particular business purpose. The rules that all assets and liabilities in foreign currency are to be converted into the currency of the share capital has one exception in the case in which the share capital was for technical reasons, expressed in a currency different from that in which it was intended to be invested. In that case, the balance sheet is to be expressed in the intended currency as soon as this becomes technically possible and the share capital from that date onward, must be converted into the intended currency at the rate of exchange in force at the date on which the conversion became first possible.